Optimization of Laser Sintering for Demineralized Bone/Polycaprolactone Composite Powder for Bone Tissue Scaffold - Mohsen Ziaee; Ayesha Mahmood; Nathan B. Crane (Journal of Manufacturing and Materials Processing, 2020)
Demineralized bone matrix (DBM) is an excellent bone scaffold material, but is available in only limited sizes. An additive manufacturing (AM) method that retains these properties while enabling customized geometry fabrication would provide bone scaffolds for a larger range of geometries while maintaining the benefits of DBM. This work examines laser sintering (LS) of a blend of demineralized bone matrix (DBM) and polycaprolactone (PCL) using a CO2 laser beam. A comprehensive experimental study was carried out to find the conditions that form defect-free layers while still retaining the favorable biological features of DBM. The results identify a process setting window over which LS can be utilized to constructing complex patient-specific scaffolds. With the identified setting, first, the DBM/PCL blend was fused in the LS machine. Parts were then were further strengthened through a post-processing heat treatment. The shrinkage level, skeletal density, mechanical testing, and porosimetry of the resultant samples were compared to traditional machined DBM blocks. The maximum tensile strength of the samples and post-processing shrinkage depends on heat treatment duration. The tensile strength measurements demonstrate that the post-processing conditions can be tuned to achieve the tensile strength of the demineralized bone strips. Evaluation of the dimensional change suggests that the shrinkage along the laser paths is ~0.3% while thickness shrinks the most (up to ~20%). The porosimetry and density studies showed that the final part achieved over 40% porosity with a density comparable to blocks of DBM.